PENGARUH IKLIM KOMUNIKASI DAN PERILAKU ORGANISASI TERHADAP KINERJA PEGAWAI (Studi pada Pegawai Negeri Sipil Dinas Kebersihan dan Pertamanan Kota Bogor) - Puspanidra, Tiara (Media Bahasa, Sastra, dan Budaya Wahana, 2016)
AbstractThis research is based on the poor performance of government employee, especially in enviromental management. Dinas Kebersihan dan Pertamanan Kota Bogor as the government institution responsible for enviromental issues that need to improve the enviromental quality so can be enjoyed by all the citizen. Employee performance can be affectted by organizational communication climate and organizational behavior, where a good communication climate can result in job satisfaction of employee. Employees who have job satisfaction tends to increase its performance. Improved performance of the individual in the end can increase the productivity of the organization. Organizational behavior can improve the ability of the manager/supervisor in understanding other/the employess. Also can improve the quality and productivity of employee with a way to show employer how to empower them, to design and implement change programs, improving service and helping employees cope with work-life conflict and establish a healthy working climate. Accordingly, this study aims to determine the extent of the influence of communication climate and organizational behavior on employees performance. This research is quantitative, using survey method, which is distributing questionnaires using saturated sampling technique or census. The result showed that there are positive relationship between organizational communication climate and organizational behavior, either partially or simultaneously on employee performance. So, in order to improve the employee performance in Dinas Kebersihan dan Pertamanan Kota Bogor, communication climate and organizational behavior also needs to improved. Keywords: Organizational Communication Climate, Organizational Behavior, Performance, Dinas Kebersihan dan Pertamanan Kota Bogor